Taxonomic revision of the geckos of the Gonatodes concinnatus complex (Squamata: Sphaerodactylidae), with description of two new species - Sturaro, Marcelo José; Avila-Pires, Teresa C. S. (Zootaxa, 2011)
The Gonatodes concinnatus complex, as here considered, consists of Gonatodes species characterized by a white suprahumeral spot with black margins; vermiculations or not on back; and transversely enlarged scales under the tail, showing the sequence 1’1’1”, and in some specimens 1’1’2” on the anterior portion. Two species are presently recognized in this Amazonian complex: G. concinnatus and G. tapajonicus. New material collected in eastern Amazonia (states of Pará and Amapá, Brazil) made it necessary to review these species. We analyzed several populations within this complex, from Colombia, Ecuador, Peru, Venezuela and Brazil, including these new records. Specimens were separated in groups defined on basis of color pattern. Stepwise discriminant function analyses were then performed to compare the external morphology (measurements and scale counts) in these groups. Results support recognition of five taxa, corresponding to G. concinnatus from western Amazonia, in Ecuador and northern Peru; G. ligiae from northwestern Venezuela (east of the Andes); G. tapajonicus, from the Tapajós river basin, in Pará, Brazil; and two new species, one from eastern Amazonia, in the states of Pará (north and south of the Amazon river) and Amapá, Brazil, and another from central Colombia, east of the Andes. Diagnoses and descriptions of all species are presented.